Genotyping of Listeria monocytogenes isolates from poultry carcasses using high resolution melting (HRM) analysis - Sakaridis, Ioannis (Biotechnol Biotechnol Equip, 2014)
An outbreak situation of human listeriosis requires a fast and accurate protocol for typing Listeria monocytogenes. Existing techniques are either characterized by low discriminatory power or are laborious and require several days to give a final result. Polymerase chain reaction (PCR) coupled with high resolution melting (HRM) analysis was investigated in this study as an alternative tool for a rapid and precise genotyping of L. monocytogenes isolates. Fifty-five isolates of L. monocytogenes isolated from poultry carcasses and the environment of four slaughterhouses were typed by HRM analysis using two specific markers, internalin B and ssrA genes. The analysis of genotype confidence percentage of L. monocytogenes isolates produced by HRM analysis generated dendrograms with two major groups and several subgroups. Furthermore, the analysis of the HRM curves revealed that all L. monocytogenes isolates could easily be distinguished. In conclusion, HRM was proven to be a fast and powerful tool for genotyping isolates of L. monocytogenes.